A review of selected pumping systems in nature and engineering—potential biomimetic concepts for improving displacement pumps and pulsation damping. (3rd September 2015) - Bach, D; Schmich, F; Masselter, T; Speck, T
Abstract: The active transport of fluids by pumps plays an essential role in engineering and biology. Due to increasing energy costs and environmental issues, topics like noise reduction, increase of efficiency and enhanced robustness are of high importance in the development of pumps in engineering. The study compares pumps in biology and engineering and assesses biomimetic potentials for improving man-made pumping systems. To this aim, examples of common challenges, applications and current biomimetic research for state-of-the art pumps are presented. The biomimetic research is helped by the similar configuration of many positive displacement pumping systems in biology and engineering. In contrast, the configuration and underlying pumping principles for fluid dynamic pumps (FDPs) differ to a greater extent in biology and engineering. However, progress has been made for positive displacement as well as for FDPs by developing biomimetic devices with artificial muscles and cilia that improve energetic efficiency and fail-safe operation or reduce noise. The circulatory system of vertebrates holds a high biomimetic potential for the damping of pressure pulsations, a common challenge in engineering. Damping of blood pressure pulsation results from a nonlinear viscoelastic behavior of the artery walls which represent a complex composite material. The transfer of the underlying functional principle could lead to an improvement of existing technical solutions and be used to develop novel biomimetic damping solutions. To enhance efficiency or thrust of man-made fluid transportation systems, research on jet propulsion in biology has shown that a pulsed jet can be tuned to either maximize thrust or efficiency. The underlying principle has already been transferred into biomimetic applications in open channel water systems. Overall there is a high potential to learn from nature in order to improve pumping systems for challenges like the reduction of pressure pulsations, increase of jet propulsion efficiency or the reduction of wear.